Implementasi Kebijakan Pemberdayaan Usaha Kecil Menengah di Dinas Koperasi dan UKM Provinsi Banten - Nurjanah, Siti; Achmad, Mansyur; Gatiningsih (Neolectura, 2024)
This research was motivated by the MINISTRY OF COOPERATIONS AND SMEs, REPUBLIC OF INDONESIA, Regional Regulation Number 02 of 2016 concerning the Empowerment of Small and Medium Enterprises in the Banten Province region. Article 9 implemented by the provincial Cooperatives and SMEs Service, the aim of this research is to determine the Implementation of the Small and Medium Enterprises Empowerment Policy in the Banten Province Cooperatives and SMEs Service, efforts to improve the community economy through empowering SMEs, are part of national economic development capable of being the main driver as development of the people's economic potential and the ability to provide economic development and the availability of employment opportunities. The qualitative method methodology used in this research is approaching qualitative analysis techniques, data collection is a combination (Tringaulasi) which is carried out in a structured manner by presenting data and drawing conclusions from the research results. There are still many obstacles to policy implementation in SME empowerment programs in the Cooperative Department and Banten Province SMEs. The results of research on the implementation of SME empowerment policies have not been optimal, it was found that there are still many SME actors who have not received access programs, both training and access to capital, so that achieving increased empowerment is not on target, resulting in less efficiency in implementing program policies, this can be seen from not being achieved according to standards. As the aim of the SME empowerment policy, the efforts that have been implemented regarding SME empowerment through supporting programs are still far from being expected to provide sanctions for policy violators, there is a lack of facilities and infrastructure so the government needs to improve the facilities and infrastructure for SMEs to support, intensify supervision and assistance, as well as encouraging more intense outreach to the community, equitable data collection on SMEs, as well as efforts to improve the community's economy.